Penerapan Konseling Kipas dalam Meningkatkan Self-Confidence - Gudnanto Gudnanto; Ramadhan Abdurrahman Wakhid (Indonesian Journal of Educational Counseling, 2026)
This study aims to improve students' low self-confidence, especially in public speaking. Researchers use individual counseling services using the KIPAS steps in the KIPAS counseling approach. The type of research is a case study to determine students' problems, namely low self-confidence, especially in public speaking. The data collection method used in this study is using observation and interviews. The results of this study are the main factors that cause students to be unconfident in public speaking is because they feel nervous, so students look confused, anxious and afraid of making mistakes when in public. This makes students unable to put together sentences in speaking in an orderly manner. The use of the KIPAS counseling approach through the KIPAS steps in individual counseling services has succeeded in helping students increase their self-confidence in public speaking, where by changing neglected assets into renewable ones, namely not being confident in public speaking into being confident in public